Effectiveness Of Variable Stent Designs For Treatment Of Renal Artery Aneurysm - Akashah, Akmal Rafiq (Universiti Sains Malaysia, 2018)
This research analyzes different stent designs that are available in the market namely Honeycomb, Coronary Stent and Medical stent to reduce the probability of Renal Artery Aneurysm (RAA) from rupturing. The purpose of this research is to help reduce the fatalities that commonly happens among pregnant due to impact of RAA. Particle Image Velocimetry (PIV) is conducted experimentally and as a mean to validate using the numerical solution for Renal Artery model. Fluid-structure-interaction (FSI) simulation using Ansys is conducted to observe the velocity vector (flow pattern), pressure contour and wall shear stress to determine the best stent design to be used in the RAA treatment. From the results, it shows that Medical stent is the best stent for RAA treatment because it can control the velocity and pressure which are 0.3m/s and 16000 Pa respectively along the renal artery and especially the bulging of the aneurysm which should show velocity of zero. Medical stent also shows controlled value of wall shear to prevent hemolysis. The standard value that could lead to hemolysis is above 50 Pa. The risk of RAA rupturing also decreases with the use of medical stent.